TECHNICAL EDUKATION AND ITS PLACE IN THE CONTEMPORARY SYSTEM OF BASIC EDUCATION - KVAPIL, Ludek; Miroslav, JANU (Trends in education, 2009)
The contribution deals with the issue of teaching technical education at basic schools, focusing on the attitude of the specialist teacher.
Keywords: technical education; child personality; technical material; the pupils´ individuality; ability; creativity; product.